Optimisation of applied loads when using the two-point method for assessing the force-velocity relationship during vertical jumps - García-Ramos, A.; Pérez-Castilla, A.; Jaric, S. (Sports Biomechanics, 2021)
This study aimed to compare the reliability and validity of the force-velocity (F-V) relationship parameters obtained from two-point methods differing in the distance between experimental points, and to evaluate the acute change in unloaded jump height after a vertical jump testing procedure based on multiple loads. Totally, 18 men randomly performed two sessions of the squat jump (SJ) and two sessions of the countermovement jump (CMJ) exercises against five external loads (17, 30, 45, 60 and 75 kg). The unloaded jump height was evaluated before and after each testing procedure. Five two-point methods (0-17, 0-30, 0-45, 0-60 and 0-75 kg) and the multiple-point method (0-17-30-45-60-75 kg) were used to model the F-V relationship. The most distant two-point method (0-75 kg) revealed a comparable reliability (CV<12.1%; ICC>0.72) and high concurrent validity (r >0.91) with respect to the multiple-point method (CV<10.9%; ICC>0.72). The reliability and validity of the two-point methods decreased with the proximity of the applied loads. Unloaded jump height was significantly reduced after both testing procedures (p <0.05). These results support the two-point method based on distant loads as a quick and less prone to fatigue procedure for testing the F-V relationship through vertical jumps.